Exploration of the Challenges in Adopting Smart Farming among Smallholder Farmers : A Qualitative Study - Zubaidah, Omar; Fazleen, Abdul Fatah; Abdul Rahman, Saili; Jamayah, Saili; Nur Masriyah, Hamzah; Rumaizah, Che Md Nor; Dayang Siti Norhafiza, Abang Ahmad (Semarak Ilmu Publishing, 2025)
The impact of climate change on global agriculture has increased the need for sustainable and resource-efficient farming practices to ensure food security. Smart farming, which incorporates the use of artificial intelligence (AI) and the Internet of Things (IoT), allows farmers to monitor changes in climatic factors and soil conditions, optimize farming operations and increase crop yields. This study aimed to identify the factors influencing the adoption of smart farming among smallholders in Peninsular Malaysia. Twelve participants were recruited using the snowball sampling method and thematic analysis was used to identify patterns and themes in the qualitative data obtained from interviews. The analysis revealed that participants desired to use smart farming technologies due to the lack of foreign labour, cost savings, time flexibility, awareness and education campaigns and government support. Utilizing smart farming technologies can result in cost savings through efficient use of inputs, reduction of waste and automation of tedious tasks. The use of solar energy can provide a dependable and affordable energy source to increase sustainability, while precision planting and seeding techniques can improve the efficient use of resources. The government's provision of information and funding has helped participants establish smart farming in their farms, with some receiving grants and collaborating with universities to develop new technologies. Overall, smart farming technologies can help farmers manage their crops and resources more effectively, increase yields and optimize farm operations